Hot-press hand injury caused by roller type ironing machine - Abdul Kerim Yapici; Umit Kaldirim; Ibrahim Arziman; Sukru Ardic; Murat Eroglu (Indian Journal of Plastic Surgery)
Thermal crush burn injury due to roller type ironing press machine is relatively rare and can cause destructive effects with significant morbidity. These injuries can be avoided by taking some basic precautions. Early debridement after admission and definitive treatment after the extent of injuryare delineated and these are the preferred approaches in the management. We present a case of thermal crush injury of the hand caused by laundry roller type ironing press machine.